1995
DOI: 10.1287/mksc.14.1.61
|View full text |Cite
|
Sign up to set email alerts
|

A High-Tech Product Market Share Model with Customer Expectations

Abstract: In a product category based on dynamic technology, new products enter the market in rapid succession, and the competitive situation changes almost daily. Because technological features of available products tend to improve while prices tend to decline, customers develop expectations that may influence their purchase decisions. We model the impact of customer expectations regarding and on product market share in the personal computer industry, finding significant nonlinear effects of both. These effects are obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…In addition to these mental simulation findings, there is also literature in marketing supporting the notion that consumers incorporate future expectations into their purchase decisions (Bridges et al 1995, Boulding et al 1993, Holak et al 1987, Jacobsen and Obermiller 1990, Winer 1985. When considering the purchase of high technology products, for example, Holak et al (1987) found that consumers incorporate their expectations of the timing of the next generation technology into their current purchase and upgrade decisions (see also Bridges et al 1995).…”
Section: Theoretical Backgroundmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to these mental simulation findings, there is also literature in marketing supporting the notion that consumers incorporate future expectations into their purchase decisions (Bridges et al 1995, Boulding et al 1993, Holak et al 1987, Jacobsen and Obermiller 1990, Winer 1985. When considering the purchase of high technology products, for example, Holak et al (1987) found that consumers incorporate their expectations of the timing of the next generation technology into their current purchase and upgrade decisions (see also Bridges et al 1995).…”
Section: Theoretical Backgroundmentioning
confidence: 90%
“…When considering the purchase of high technology products, for example, Holak et al (1987) found that consumers incorporate their expectations of the timing of the next generation technology into their current purchase and upgrade decisions (see also Bridges et al 1995). With respect to price, Jacobsen and Obermiller (1990) found that consumers incorporate future price expectations into their current time period purchase decisions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to Zeithaml et al [64], customers' expectations can be defined as their beliefs about a product, which they use as a reference point or standard to assess its performance. Prior studies show that customers' expectations can affect their purchase decisions [11] as well as their level of post-purchase satisfaction because they compare their expectations with the product's actual performance in their evaluation of product quality [63,64].…”
Section: Hypothesesmentioning
confidence: 99%
“…However, such a simple comparison of coefficient estimates can be misleading, and thus, we compute scalefree elasticities to compare the responsiveness of prices to positive and negative e-sentiments. 11 In a hedonic regression setting, price elasticity with respect to esentiment can be interpreted as the percent change in consumers' willingness-topay, given a one percent increase in (positive/negative) e-sentiment. Table 5 (Column 2) illustrates that a 1 % increase in positive (negative) e-sentiment leads to a .014 % increase (.025 % decrease) in price.…”
Section: Competition and E-sentiment Effectsmentioning
confidence: 99%
“…hardware and software). Some other papers that focus on interesting aspects of the new product adoption process are by Souza, Bayus, and Wagner (2004), Song (2003), Smith (1986), Golder and Tellis (1997), Bridges, Yim, and Briesch (1995), Narasimhan (1989) and Lee and Connor (2003).…”
Section: Introductionmentioning
confidence: 99%